Templates for Authorship : American Women's Literary Autobiography of the 1930s - Petrie, Windy Counsell; Petrie, Windy Counsell (Book collections on Project MUSE., 2021)
"As autobiographies by famous women like Eleanor Roosevelt and Amelia Earhart became bestsellers in the 1930s, American publishers sought out literary autobiographies from female novelists, poets, salon hosts, and editors. Templates for Authorship analyzes the market and cultural forces that created an unprecedented boom in American women's literary autobiography. Windy Counsell Petrie considers twelve autobiographies from a diverse group of writers, ranging from highbrow modernists such as Gertrude Stein and Harriet Monroe to popular fiction writers like Edith Wharton and Edna Ferber, and lesser known figures such as Grace King and Carolyn Wells. Since there were few existing examples of women's literary autobiography, these writers found themselves marketed and interpreted within four cultural templates: the artist, the activist, the professional, and the celebrity. As they wrote their life stories, the women adapted these templates to counter unwanted interpretations and resist the sentimental feminine traditions of previous generations with innovative strategies of deferral, elision, comedy, and collaboration. This accessible study contends that writing autobiography offered each of these writers an opportunity to define and defend her own literary legacy"